Colposcopy Value in Young Child-bearing Women: Is New Recommendations Necessary? - Fahimeh Sabet; Avishan Aminizad; Fariba Behnamfar; Tajossadat Allameh; Seyedeh Ghazal Shahrokh; Rostami Koushan; Amirmohammad Taravati; Leila Mousavi Seresht (Advanced Biomedical Research)
Background: Cervical cancer is a common malignancy in women and HPV infection is directly linked to it and can be considerably prevented through routine screenings. Despite the belief about the persistence of HPV infection in older than 30-year-old women, high-grade lesions might be detected in younger ages; therefore, the purpose of the current study is to determine the worth of HPV infection screening in younger than 30-year-old women. Materials and Methods: This cross-sectional study has been executed on 100 under 30-year-old women who have undergone genotyping. Fourteen HPV subtypes including HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68 were defined as high risk and the patients were categorized in HPV 16/18 or other high-risk groups. Pap smear and colposcopy were performed for both groups and interpreted as normal, low-risk and high-risk lesions and compared between the groups. Results: In terms of demographic, clinical, and sexual behavioral characteristics, the present study exhibited similarity (P value > 0.05). Pap smear (P value = 0.100) and colposcopy (P value = 0.711) grading did not differ between those with HPV 16/18 versus other high-risk HPV patients. Pap smear and colposcopic findings were weekly in agreement (κ < 0.5, P value < 0.001). Conclusion: Early cytological plus genotyping assessment in women at early child-bearing ages seems logical, as the cervical premalignant lesions have a slow progressing nature and can be easily treated in early stages.